A Public Expenditure Review for Paraguay : The Quest for Optimal Tax and Expenditure Policies for Shared Prosperity - World Bank (Washington, DC, 2015)
Paraguay has achieved significant progress in terms of fiscal policy over the past decade. Despite this progress on fiscal reform, three major challenges remain: 1) a volatile macroeconomic environment; 2) still insufficient fiscal resources; and 3) high levels of poverty and inequality. In light of these three challenges, the objective of this report is to examine the extent to which fiscal policy in Paraguay has contributed to the social progress of the past decade, and can serve the purpose of further reducing poverty and enhancing shared prosperity in the years to come. Overall, fiscal policy can contribute to containing poverty and inequality by buffering the negative impact of financial and economic crises on vulnerable parts of the population. Moreover, tax and expenditure policies that redistribute from high- to low-income households in a well-targeted manner can also contribute to these goals. The current structure of the tax system appears suboptimal in light of the identified challenges. Even though the reliance on indirect taxes insulates public revenues from economic volatility to a certain extent, it imposes high costs associated with sufficiency and equity of the system. Adequate taxation of the agricultural sector is needed to level the playing field for business development in all sectors and to address the insufficiency of taxes. While fiscal policy contributes less to poverty reduction and shared prosperity in Paraguay than in the other countries analyzed for this study, direct transfers are well targeted. Overall, Paraguay's fiscal system is less progressive than in other Latin American countries analyzed. Paraguay's reliance on indirect taxes makes its overall tax system regressive. The sufficiency and efficiency of social expenditures have to be considered within the context of fiscal prudence, which is a continuous task. This is especially important in light of the recent expansionary fiscal stance. Only if the Government is able to sustain fiscal prudence in the future, will it be able to maintain macroeconomic stability and performance.